2022
DOI: 10.3389/fmars.2022.932446
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexation, FT-IR characterization, and plankton abundance in the marine surface microlayer of coastal areas in the Eastern Mediterranean

Abstract: Barely any data exist on metal speciation in the marine surface microlayer (SML), a rather complex environment, the study of which contributes to enhancement of knowledge on metal speciation and its effect to the ocean. Metal speciation is significant since life requires a wide variety of trace metals that are essential for the growth of the organisms. Ligand concentrations (L) of copper (Cu), zinc (Zn), and cadmium (Cd) were studied by anodic stripping voltammetry (ASV) in the SML of coastal areas within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…To our knowledge, the electrochemical study of Cu-binding organic ligands in the SML has only been reported for a few marine areas. In Table 4, we compared obtained Middle Adriatic CuCC parameters, EF-s, and L tot /DOC ratios for the SML and corresponding ULW with those published for the Mediterranean Sea, 49,50,57 the Norwegian ords, 48 and the Yellow Sea, 58 taking into account their specic environment and trophic conditions. The range of L tot concentrations found for the SML in the middle Adriatic Sea is comparable to the values reported for the oligotrophic E Mediterranean Sea, but is lower than the L tot concentrations in the SML in the mesotrophic NW Mediterranean Sea, which is considered the second most productive part of the Mediterranean area due to nutrient supply from the Rhone and Ebro rivers.…”
Section: Cucc In the Surface Seawater Of The Middle Adriatic Seamentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the electrochemical study of Cu-binding organic ligands in the SML has only been reported for a few marine areas. In Table 4, we compared obtained Middle Adriatic CuCC parameters, EF-s, and L tot /DOC ratios for the SML and corresponding ULW with those published for the Mediterranean Sea, 49,50,57 the Norwegian ords, 48 and the Yellow Sea, 58 taking into account their specic environment and trophic conditions. The range of L tot concentrations found for the SML in the middle Adriatic Sea is comparable to the values reported for the oligotrophic E Mediterranean Sea, but is lower than the L tot concentrations in the SML in the mesotrophic NW Mediterranean Sea, which is considered the second most productive part of the Mediterranean area due to nutrient supply from the Rhone and Ebro rivers.…”
Section: Cucc In the Surface Seawater Of The Middle Adriatic Seamentioning
confidence: 99%
“…The range of L tot concentrations found for the SML in the middle Adriatic Sea is comparable to the values reported for the oligotrophic E Mediterranean Sea, but is lower than the L tot concentrations in the SML in the mesotrophic NW Mediterranean Sea, which is considered the second most productive part of the Mediterranean area due to nutrient supply from the Rhone and Ebro rivers. 59 The biological molecules and products formed during the rapid transformation of fresh organic matter are the predominant Cu-binding ligands in the SML of the E Mediterranean, 50,57 while there may be autochthonous as well as additional sources of ligands such as atmospheric inputs in the SML of the NW Mediterranean. 49 The average values for L tot concentrations in the ULW of the Adriatic Sea were up to ve times lower than those in the E and NW Mediterranean, con-rming the low autochthonous production of ligands.…”
Section: Cucc In the Surface Seawater Of The Middle Adriatic Seamentioning
confidence: 99%
“…TEs enter the sea mostly through the river discharges, either adsorbed onto inorganic and organic suspended particles or in dissolved form (Remeikaite-Nikienėet al, 2018;Sun et al, 2020). Dissolved TEs rapidly come into the particulate phase, e.g., via adsorption onto suspended particles, precipitation, flocculation (Karbassi et al, 2014;Karavoltsos et al, 2022). TEs associated with inorganic and organic suspended matter settle and accumulate in sediments, but they can be remobilized and released into the water under specific conditions, being more available to the biota, which could have significant detrimental effects on the ecosystem and human health (Omar et al, 2015;Oros, 2019).…”
Section: Introductionmentioning
confidence: 99%